A leitura e o digital: o nascimento de uma cultura pós-literária no Brasil - Florence Dravet; Gustavo de Castro (Caravelle)
Based on the “Portraits of reading in Brazil” by the Institute Pró-Livro, the relations between orality, scripturality and visuality in Brazilian culture are discussed. We approach the issue of digital reading in the light of initial researches presented by Wolf (2019) and make an assumption of a post-literary culture in formation in Brazil that needs protection for the preservation and development of reading and imagination skills.